REENGINEERING LOGISTICS BUSINESS PROCESSES IN MODERN ORGANIZATIONS (Development Service Industry Management, 2024)
The purpose of the article is to analyze the theoretical and practical aspects of implementing reengineering in the logistics systems of modern organizations. The article discusses the impact of globalization, digital technologies, and the growth of data on logistics management, and identifies the role of business process reengineering in ensuring the efficiency and competitiveness of organizations. Logistics business process reengineering is a strategic approach that involves radically rethinking and redesigning existing processes to achieve significant improvements in productivity, customer service, and adaptation to changes in the business environment. The authors analyze the stages of reengineering implementation, among which the most important are diagnostics of existing processes, development of new process models, integration of digital technologies, change management, and performance evaluation. Particular attention is paid to the importance of digitalizing business processes, which allows organizations not only to automate processes but also to create personalized customer interaction that meets modern market requirements. The introduction of innovations such as IoT, blockchain, ERP systems, and artificial intelligence can significantly improve the efficiency of logistics operations and reduce costs. The article also discusses the importance of moving from traditional functional management to system integration, which allows for optimized delivery times, improved product and service quality, and better transportation and warehousing processes. In Ukraine, the process of implementing reengineering of logistics business processes is actively developing, and the experience of individual organizations shows positive results, in particular in terms of increasing competitiveness and stability. As a result, the successful implementation of logistics process reengineering requires not only changes in technology, but also a comprehensive transformation of management approaches and corporate culture, which allows organizations to respond effectively to changes in the market environment.
Keywords: reengineering; logistics business processes; digitalization; information technology; competitiveness; automation; optimization